Enhanced Efficiency of Dye–sensitized Solar Cells Based on Bulk Synthesized TiO2 Nanorods Annealed at Different Temperatures. Issue 9 (7th September 2015) - Sayahi, Hani; Hamadanian, Masood; Mohsenzadeh, Farshid; Aghapoor, Kioumars; Kiani, Mohammad Ali
Abstract In this study, bulk TiO2 nanorods are synthesized by hydrothermal method in order to be used in the dye‐sensitized solar cells (DSSCs). These nanorods are annealed at different temperatures and deposited electrophoretically. The influence of post heat treatment has been thoroughly investigated on fabricated DSSCs using electrochemical impedance spectroscopy (EIS). The results have revealed that the diameter, size and density of the prepared bulk nanorods are function of annealing temperatures. Optimization of the prepared DSSCs has led to an improved efficiency (ca. 3.82%) under AM 1.5 simulated sunlight.